How much collocation knowledge do L2 learners have?: the effects of frequency and amount of exposure - González Fernández, Beatriz; Schmitt, Norbert (John Benjamins Publishing, 2015)
Many scholars believe that collocations are difficult to learn and use by L2 learners. However, some research suggests that learners often know more collocations than commonly thought. This study tested 108 Spanish learners of English to measure their productive knowledge of 50 collocations, which varied according to corpus frequency, t-score, and MI score. The participants produced a mean score of 56.6% correct, suggesting that our learners knew a substantial number of collocations. Knowledge of the collocations correlated moderately with corpus frequency (.45), but also with everyday engagement with English outside the classroom, in activities like reading, watching movies/TV, and social networking (composite correlation = .56). Everyday engagement also had a stronger relationship with collocation knowledge than years of English study (.45).